Multiple neurofibromas as the presenting feature of familial atypical multiple malignant melanoma (FAMMM) syndrome. Issue 6 (23rd April 2013) - Vanneste, Rachel; Smith, Erika; Graham, Gail
Abstract Mutations in the cyclin‐dependent kinase inhibitor‐2A (CDKN2A) gene have been associated with a number of malignancies, most notably cutaneous malignant melanoma (CMM). Mutations in this gene have also been associated with pancreatic cancer and breast cancer, as well as astrocytomas and other nervous system tumors (NST). Among NST, rare solitary internal neurofibromas have been reported, but multiple cutaneous neurofibromas have only been described in two families. In the first family, the affected individuals all carried a heterozygous G > C mutation at the splice acceptor site of intron 1 resulting in skipping of CDKN2A exon 2, while the affected individuals in the second family had a deletion that encompassed the whole CDKN2A/CDKN2B/ANRIL locus. We now report on a proposita presenting with multiple biopsy‐proven cutaneous neurofibromas and a solitary spinal neurofibroma found to have a deletion of 14 nucleotides in exon 2 of CDKN2A, providing further evidence that p14, p16, and/or ANRIL are specifically involved in the pathogenesis of neurofibromas as a feature of the familial atypical multiple malignant melanoma spectrum. © 2013 Wiley Periodicals, Inc.